Efektivitas Lemon (Citrus Limon) Sebagai Reagen Alternatif Pemeriksaan Proteinuria - eli yusrita; Yufitriah nursaih (LPPM Universitas Abdurrab, 2023)
Proteinuria is the presence of protein in human urine that exceeds the normal value, which is more than 150 mg 24 hours or in children more than 140 mg mÂ². Proteinuria is also a sign of kidney damage and acts as a sign of cardiovascular mortality risk and a predictor of progression of kidney disease. measuring the presence of protein content in urine where the administration of acetic acid can die to reach the protein isoelectric point, with heating it causes denaturation and precipitation occurs Lemon (citrus limon) is a plant that has benefits as a natural antioxidant latena contains vitamin C acetic acid, essential oils, coumarins from this study to determine the effectiveness of lemon juice solution (Curus limon) as an alternative urine protein reagent with concentrations of 20% 40%, 60%, 80% and 100% The method used in this study was experimental. obtained is 3 at a concentration of 20%, 40% and 60%, 80%, and 100%. The conclusion of this study is that a solution of lemon juice (Cruz ammon) with a concentration of 20%, 40%, 60, 80%, and 100% is effective as alternative reagent for proteinuria.